Increased Serum Type I Interferon Activity in Organ-Specific Autoimmune Disorders: Clinical, Imaging, and Serological Associations - Mavragani, Clio; Niewold, Timothy B.; Chatzigeorgiou, Antonis; Danielides, Stamatina; Thomas, Dimitris; Kirou, Kyriakos; Kamper, Elli; Kaltsas, Gregory A.; Crow, Mary (Frontiers in Immunology, 2013)
Background: Activation of the type I interferon (IFN) pathway has been implicated in the pathogenesis of systemic autoimmune disorders but its role in the pathogenesis of organ-specific autoimmunity is unknown. We tested the hypothesis that endogenous expression of type I IFN functional activity contributes to the pathogenesis of autoimmune thyroid disease (ATD) and type I diabetes (T1DM). Methods: We studied 39 patients with ATD and 39 age and sex matched controls along with 88 T1DM patients and 46 healthy matched controls respectively. Available clinical and serological parameters were recorded by chart review, and thyroid ultrasound was performed in 17 ATD patients. Type I IFN serum activity was determined in all subjects using a reporter cell assay. The rs1990760 SNP of the interferon-induced helicase 1 gene (IFIH1) was genotyped in ATD patients. Results: Serum type I IFN activity was increased in patients with ATD and T1DM compared to controls (p-values: 0.0018 and 0.04, respectively). ATD patients with high type I IFN serum activity had increased prevalence of antibodies against thyroglobulin and cardiopulmonary manifestations compared to those with low IFN activity. Additionally, the presence of micronodules on thyroid ultrasound was associated with higher type I IFN levels. In patients with T1DM, high IFN levels were associated with increased apolipoprotein B levels. Conclusions: Serum type I IFN activity is increased in ATD and T1DM and is associated with specific clinical, serological and imaging features. These findings may implicate type I IFN pathway in the pathogenesis of organ specific autoimmunity.